Sporulation conditions influence the surface and adhesion properties of Bacillus subtilis spores - Hamiot, Audrey; Lemy, Christelle; Krzewinski, Frederic; Faille, Christine; Dubois, Thomas (Frontiers in Microbiology, 2023)
Spore-forming bacteria of the Bacillus subtilis group are responsible for recurrent contamination of processing lines in the food industry which can lead to food spoilage. The persistence of B. subtilis would be due to the high resistance of spores to extreme environmental condition and their propensity to contaminate surfaces. While it is well known that sporulation conditions modulate spore resistance properties, little is known about their effect on surface and adhesion properties. Here, we studied the impact of thirteen sporulation conditions on the surface and adhesion properties of B. subtilis 168 spores. We showed that Ca 2+ or Mg 2+ depletion, lower oxygen availability, acidic pH as well as oxidative stresses during sporulation lead to the release of more hydrophobic and adherent spores. The consequences of these sporulation conditions on crust composition in carbohydrates and proteins were also evaluated.The crust glycans of spores produced in a sporulation medium depleted in Ca 2+ or Mg 2+ or oxygen-limited conditions were impaired and contained lower amounts of rhamnose and legionaminic acid. In addition, we showed that lower oxygen availability or addition of hydrogen peroxide during sporulation decreases the relative amount of two crust proteins (CgeA and CotY) and the changes observed in these conditions could be due to transcriptional repression of genes involved in crust synthesis in late stationary phase. The fact that sporulation conditions affect the ease with which spores can contaminate surfaces could explain the frequent and recurrent presence of B. subtilis spores in food processing lines.